Demonstration of 108 Gb/s Duo-Binary PAM-8 Transmission and the Probabilistic Modeling of DB-PAM-M BER - Md Ghulam Saber; Ramon Gutierrez-Castrejon; Zhenping Xing; Md Samiul Alam; Eslam El-Fiky; Daniel E. Ceballos-Herrera; Fabio Cavaliere; Gemma Vall-Llosera; Stephane Lessard; David V. Plant (IEEE Photonics Journal, 2021)
We report 108 Gb/s Duo-Binary PAM-8 (DB-PAM-8) transmission using direct-detection aided by Volterra equalizer. The bit-error-rate (BER) performance of the DB-PAM-8 signal has been evaluated through error counting by varying the bit rate, received optical power, and reach. The experimental results suggest that up to 108, 102, and 84 Gb/s signals can be propagated in back-to-back (B2B), and over 10, and 20 km of standard single-mode fiber (SMF), respectively, below the low-density parity-check forward error correction (LDPC-FEC) threshold. Furthermore, we derive a probabilistic model of the BER for multilevel DB-PAM-M signaling that is verified using our measurements. The model of this important performance metric turned out to be accurate enough, especially at low BER values, where its use is more convenient.